Approaching the EUropean federation? - Dosenrode-Lynge, Sören Zibrandt von (Federalism studies, 2016)
The European project has, within only 52 years, achieved a surprising momentum, and the European Union is now approaching full statehood. The Convention on the Future of Europe has finished its work and handed over a proposal for a constitutional treaty to the Heads of State and Government of the EU. It is therefore the ideal time to present an integrated analysis of what appears to be the emerging European State. This key volume therefore discusses the central questions and concepts within the field of European studies, which include federalism, the relationship between statehood and constitution, integration and constitution, the regions in the 'new' Europe and the EU as an international actor. These discussions are then developed and analyzed in relation to the draft constitution. Timely and insightful, the volume is suitable for courses on European integration, federalism and international politics.